Predictors and classifications of the degree of severity of acute pancreatitis - A. V. Fedorov; V. N. Ektov; M. A. Khodorkovskiy (Вестник хирургии имени И.И. Грекова)
Severe acute panreatitis is a life-threatening disease with mortality rates of about 15%. With the development of infected necrotizing pancreatitis, complicated by the development of organ failure, the mortality rate is 35.2%. Due to the fact that acute pancreatitis is a highly variable pathological process, leading to a wide range of clinical outcomes, predicting the severity of the disease and early identification of patients at risk of developing severe complications is critical to optimize treatment outcomes for this disease. Currently, there are no uniquely accurate and practically available laboratory tests to predict the severity of patients with acute pancreatitis. The review presents literature data on the terminology and classifications of the severity of acute pancreatitis, taking into account the possibilities of their practical application. Information on clinical scale systems for assessing the severity of acute pancreatitis with an assessment of their effectiveness in predicting various treatment outcomes is presented in detail. The characteristics and capabilities of various laboratory markers in the assessment of organ failure and diagnosis of systemic complications of acute pancreatitis are presented. Currently, for the best assessment of the severity of acute pancreatitis, it is necessary to use a multidisciplinary clinical examination of patients and a combination of various predictive tools.